Prescription Patterns of Antihypertensive Drugs at Tertiary Care Hospital: A Descriptive Cross Sectional Study - Lamsal, Kamal Sharma; Neupane, Keshav Raj; Kafle, Rajati Sharma (Journal of Nobel Medical College, 2020)
Background: Hypertension is leading cause of deaths in the world. It is a modifiable and major risk factor for cardiovascular, renal and brain diseases. This study was done to see the current trend of prescription patterns of antihypertensive drugs in a tertiary care hospital in Nepal. Materials and Methods: Observational cross sectional study was done in the patients with hypertension from September 2018 to September 2019 in the department of Medicine of Civil Service Hospital, a tertiary care hospital in Kathmandu, Nepal. A total of 242 Patients who were undergoing antihypertensive treatment were included. All calculations and statistical analyses are processed by the SPSS 25.0. Results: Out of 242 prescriptions, 135(55.8%) were males, and 107(44.2%) were females. Among them, 49 (20.2%) patients had controlled Blood Pressure, 63(26%) patients had hypertension stage I and the remaining 130 patients (53.7%) patients had stage II hypertension. In the present study, 133 (54.96%) were treated with monotherapy while, 71 (29.33%) patients were prescribed with dual therapy. The most frequently prescribed drug as monotherapy was Calcium Channel Blocker in 71(53.3%) patients followed by Angiotensin Receptor Blockers in 38 (28.6%) and thiazide diuretics in 21 (15.7%) patients. Calcium Channel Blockers with Angiotensin Receptor Blockers was the most prescribed combination in 44 (62.1%) patients followed by Angiotensin Receptor Blockers and Thiazide Diuretics in 19 (26.8%) patients. Conclusion: Calcium channel blockers are the highest among the drugs that are used as monotherapy. In combination therapy, Calcium channel blockers with angiotensin receptor blocker and angiotensin receptor blockers with thiazide diuretics are the frequently prescribed drugs.